The vocation of political theory: principles, empirical inquiry and the politics of opportunity - Stears, M (SAGE Publications, 2005)
What is the purpose of political theoretical endeavour and what methods should the early 21st-century political theorist employ? These questions - which touch on issues which go to the very heart of the vocation of political theory - have become increasingly contentious in recent years. The period since the late 1980s has been one in which theorists have increasingly disagreed not only about conventional matters of normative contention but also about the means by which to seek to resolve them. This article examines a central tension that has characterized that general methodological disagreement, namely the place of empirical inquiry within the repertoire of the professional political theorist. Having carefully examined the contentions of an eclectic range of contributors to the debate, including G. A. Cohen, Alasdair MacIntyre and David Miller, this article argues that efforts either wholly to separate empirical investigation from normative enquiry or to bind the two ever-closer together are fraught with difficulties. It concludes by contending that political theorists ought to take aspects of the empirical political and social sciences extremely seriously while avoiding the temptation to have their normative agenda dictated to them by the contingen pressures of the here and now.